Stereological study of acinar growth in the rat parotid gland induced by isoproterenol - Onofre, Mirian Aparecida [UNESP]; DeSouza, L. B.; Campos, A.; Taga, R. (Elsevier B.V., 1997)
The growth of the rat parotid gland induced by daily treatment with isoproterenol (IPR) for 2 weeks was investigated by stereological methods applied to light microscopy. After 7 days of treatment, the glandular mass presented a 286% growth, with the first 3 days being the period of greatest growth. Total acinar volume exhibited a 363% increase during the period from 0 to 7 days, while acinar-cell volume presented a 468% growth from 0 to 5 days of treatment. on the other hand, total acinar-cell number did not increase during the study period. Thus, under the conditions used, IPR-stimulated gland growth wits essentially hypertrophic. However, a significant increase in the number of bipolar and multipolar mitoses was also observed, especially on the third and fifth days of treatment. As no increase in acinar-cell number occurred during growth, the presence of these mitoses suggests that cell death occurred during gland growth. on this basis, bipolar mitoses may occur to replace cells that probably degenerated during treatment, whereas multipolar mitoses may lead to the occurrence of polyploidy. (C) 1997 Elsevier B.V. Ltd.
Keywords: isoproterenol; hypertrophy; hyperplasia; acini; salivary gland; parotid gland; stereology